Hypochlorous acid triggered fluorescent probes for in situ imaging of a psoriasis model. Issue 27 (23rd June 2022) - Wei, Peng; Guo, Yu; Liu, Lingyan; Zhou, Xiaojun; Yi, Tao
Abstract : Two turn-on fluorescent probes based on Oxazine 1 were developed for the detection of HOCl. The selected probe G2 can not only detect basal HOCl in HL-60 cells, but also identify HOCl in a mouse model imiquimod induced psoriasis. Abstract : Psoriasis is a common skin disease with complex pathogenesis that lacks diagnostic methods. Typically, psoriasis is an inflammation-related disease accompanied by high expression of reactive oxygen species (ROS) in the infected part. However, due to the lack of suitable tools, it is difficult to identify the ROS, especially certain types of ROS ( e.g., HOCl) in the psoriasis model. Here, two HOCl-specific fluorescent probes, G1 and G2, were designed and synthesized based on oxazine 1. Both probes could react with HOCl with high selectivity among other ROS under physiological conditions. The selected probe G2 could detect HOCl in HL-60 cells without special stimulation and detect endogenously produced HOCl in the mouse model of arthritis. Thus, G2 was used to identify and image HOCl in situ in the imiquimod induced psoriasis model. The result showed that HOCl was a potential pathological marker of psoriasis.